Research on the Core Employment Ability of University Students in Applied Universities and the Promotion Path of Employment Guidance Work in the New Era — Taking Chengdu Technological University as an Example - Long Yan (Journal of Advanced Research in Education, 2025)
To enhance the core employability of college students in application-oriented universities and optimize the employment guidance work in universities. This study takes Chengdu Technological University as an example and conducts a systematic analysis of the current situation of students’ employability and the problems existing in the employment guidance services. The study discovers that there are still deficiencies in students’ innovation ability, interdisciplinary ability and workplace adaptability during the employment guidance process of the university. The research findings indicate that strategies such as deepening College-enterprise cooperation, implementing personalized employment guidance services, and strengthening innovation and entrepreneurship education can enhance students’ core employability and improve the employment guidance work in universities.